2022
DOI: 10.1177/20414196221115869
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of blast loading through blast–obstacle interaction

Abstract: Obstructing the passage of blast waves is an effective method of mitigating blast pressures downstream of the obstacle. To this end, the interaction between a blast wave and a simplified structural shape, such as a cylinder, has been widely investigated to understand the complex flow pattern that ensues around the obstacle. The patterns include the interference zones of the incident wave, the diffracted wave, and other secondary waves in the downstream region. Such zones are responsible for causing significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It has been shown that single obstacles [82] and an array of multi-scale (pre-fractal) obstacles [83] can lead to considerable blast wave attenuation through shock disruption and vortex shedding. Up to 14% and 26% reductions in loading were seen for the single and multiple obstacles, respectively.…”
Section: Alternative Protective Methodsmentioning
confidence: 99%
“…It has been shown that single obstacles [82] and an array of multi-scale (pre-fractal) obstacles [83] can lead to considerable blast wave attenuation through shock disruption and vortex shedding. Up to 14% and 26% reductions in loading were seen for the single and multiple obstacles, respectively.…”
Section: Alternative Protective Methodsmentioning
confidence: 99%
“…1991 ;Turcotte, 1988), (2) the presence of multiple length scales (Higham and Brevis, 2018;Higham et al, 2021;Higham and Vaidheeswaran, 2022) and (3) their higher surface area per unit volume (Werner and Ganguly, 2003). All these characteristics make fractals potentially suitable candidates for efficient blast mitigation in the urban environment.…”
Section: Scientific Motivationmentioning
confidence: 99%
“…1Incident shock strength has been shown to be a significant parameter when quantifying the blast attenuation of a single obstacle (Alshammari et al, 2022)…”
mentioning
confidence: 99%